The pursuit of balance in sequential randomized trials. (June 2016) - Guiteras, Raymond P.; Levine, David I.; Polley, Thomas H.
Abstract: In many randomized trials, subjects enter the sample sequentially. Because the covariates for all units are not known in advance, standard methods of stratification do not apply. We describe and assess the method of D A -optimal sequential allocation (Atkinson, 1982 ) for balancing stratification covariates across treatment arms. We provide simulation evidence that the method can provide substantial improvements in precision over commonly employed alternatives. We also describe our experience implementing the method in a field trial of a clean water and handwashing intervention in Dhaka, Bangladesh, the first time the method has been used. We provide advice and software for future researchers.